2023
DOI: 10.3390/land12040797
|View full text |Cite
|
Sign up to set email alerts
|

Land Transfer or Trusteeship: Can Agricultural Production Socialization Services Promote Grain Scale Management?

Abstract: Grain Scale Management (GSM) is a crucial factor in ensuring national food security. However, in countries facing rigid resource constraints and complex land tenure relationships, the strategy of promoting large-scale grain management through land management rights transfer may not be sustainable. Therefore, based on the traditional agricultural division of labor theory, we analyze the mechanism and rationality of Agricultural Production Socialization Services (APSS) with scale characteristics to promote GSM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The study found that agricultural socialization services can promote farmers' grain cultivation behavior, thus contributing positively to national food security. This result is consistent with H1 and is in line with the main points of some recent studies [17,21,23]. In all aspects of agricultural production, other things being equal, the proportion of grain grown by farmers who use socialized services in plowing, sowing, fertilizing, medicating, irrigation, and harvesting increases by 42.5%, 29.5%, 29.3%, 24.1%, 31.6%, and 53.5%, respectively, compared to those who do not use socialized services.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The study found that agricultural socialization services can promote farmers' grain cultivation behavior, thus contributing positively to national food security. This result is consistent with H1 and is in line with the main points of some recent studies [17,21,23]. In all aspects of agricultural production, other things being equal, the proportion of grain grown by farmers who use socialized services in plowing, sowing, fertilizing, medicating, irrigation, and harvesting increases by 42.5%, 29.5%, 29.3%, 24.1%, 31.6%, and 53.5%, respectively, compared to those who do not use socialized services.…”
Section: Discussionsupporting
confidence: 93%
“…The process is complex, and the cost of supervision is high. The current grain cultivation has a more mature and perfect production technology and operational processes that facilitate large-scale batch operation of machinery [23]. This is conducive to the service organization undertaking a wider range of grain growers in the production service business.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural production risk is an important reason why farmers become poor and find it difficult to escape poverty [29]. The adoption of agricultural machinery socialization services by farmers can effectively avoid agricultural production and operation risks [30], reduce the risk probability, and alleviate relative poverty. Firstly, the adoption of social agricultural machinery services can effectively deal with the harm caused by natural disasters and other emergencies that affect agricultural production, ensure agricultural output, stabilize planting income [31], reduce the loss of agricultural operating income, and alleviate the relative poverty of farmers.…”
Section: Role Of Risk In the Impact Of The Adoption Of Agricultural M...mentioning
confidence: 99%
“…With the support and guidance of a series of relevant policies such as "the Guiding Opinions on Accelerating the Development of Agricultural Producer Services" enacted in 2017 by The Ministry of Agriculture, the National Development and Reform Commission and the Ministry of Finance, China's APTS has developed rapidly, and the economic effects of service scale operation have gradually emerged [15]. Different from the path of promoting large-scale land management through land transfer, APTS can supplement and answer the questions of "who will farm", and "how to farm", effectively alleviating the problems of "being unable to farm" and "bad to farm" under the premise of maintaining the distribution of land management rights, and promoting the development of service-driven large-scale operation, thus solving the current inherent contradiction between "small production" and "big market" [16]. According to the characteristics of China's agricultural development, the APTS has overcome the bottleneck of small farmer grain planting, promoted the unity of grain production and quality improvement, and gradually become the main way to stabilize the strategic foundation of China's food security.…”
Section: Introductionmentioning
confidence: 99%